Workshop on New Mandarin Varieties - Aleza, Pablo (2017)
Very active programs to produce new mandarin varieties are being carried out in several countries using different approaches and technologies (diploid and triploid breeding, irradiation, somatic hybridization, genetic transformation, etc.). The objective of this workshop was to discuss about the most important breeding methods, the main limitations of the different approaches and methodologies, which is the challenge of new mandarin varieties in the next future and also their relationship with the legislation related to essentially derived varieties that in some cases may preclude the protection of breeder’s rights of new varieties.